2017
DOI: 10.11646/zootaxa.4363.4.6
|View full text |Cite
|
Sign up to set email alerts
|

The marbled crayfish (Decapoda: Cambaridae) represents an independent new species

Abstract: Marbled crayfish are a globally expanding population of parthenogenetically reproducing freshwater decapods. They are closely related to the sexually reproducing slough crayfish, Procambarus fallax, which is native to the southeastern United States. Previous studies have shown that marbled crayfish are morphologically very similar to P. fallax. However, different fitness traits, reproductive incompatibility and substantial genetic differences suggest that the marbled crayfish should be considered an independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 24 publications
10
53
0
Order By: Relevance
“…The peculiar marbled crayfish are triploid descendants of the sexually reproducing slough crayfish (Procambarus fallax; Martin et al 2010, Lyko 2017, Gutekunst et al 2018. Marbled crayfish represent the only known decapod crustacean capable of apomictic parthenogenesis (Scholtz et al 2003, Seitz et al 2005.…”
Section: Model Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peculiar marbled crayfish are triploid descendants of the sexually reproducing slough crayfish (Procambarus fallax; Martin et al 2010, Lyko 2017, Gutekunst et al 2018. Marbled crayfish represent the only known decapod crustacean capable of apomictic parthenogenesis (Scholtz et al 2003, Seitz et al 2005.…”
Section: Model Organismsmentioning
confidence: 99%
“…The peculiar marbled crayfish are triploid descendants of the sexually reproducing slough crayfish ( Procambarus fallax ; Martin et al. , Lyko , Gutekunst et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…1a) is a freshwater crayfish species 5 that holds a unique position among decapod crustaceans due to its parthenogenetic mode of reproduction 6 . Marbled crayfish are descendants of the sexually reproducing slough crayfish Procambarus fallax and reproduce by apomictic parthenogenesis 7,8 .…”
mentioning
confidence: 99%
“…The muscle tissue of 44 marbled crayfish P. virginalis (Lyko, 2017) was used in the study to investigate the influence of heavy metal ions on viability and metabolic enzyme activity. Crayfish were divided into 4 groups (n = 15).…”
Section: Methodsmentioning
confidence: 99%
“…Marbled crayfish Procambarus virginalis (Lyko, 2017) (earlier known as parthenogenetic form of Procambarus fallax f. virginalis Martin et al, 2010) (Decapoda, Cambaridae) are parthenogenetic crustaceans, found in 1990 in the German reservoirs [10][11][12][13]. Marbled crayfish was previously described as a subspecies of the American species Procambarus fallax (Hagen, 1870), the natural area of which covers the waters of Georgia and Florida (USA) [14,15].…”
Section: Introductionmentioning
confidence: 99%